Brazilian retail banking and the 2008 financial crisis: Were the government-controlled banks that important? - Pereira, Claudiney M.; Maia-Filho, Luiz F. (Journal of Banking & Finance, 2013)
We revisit the interest rate pass-through effect using weekly retail banking data from May 2006 to March 2010. Our choice of data avoids caveats of previous studies concerning excessive data aggregation and the estimation of how fast changes in benchmark interest rates impact those charged on short-term loans in Brazil. Our analysis focuses on four large retail banks – two of them privately owned and run, two of them government-controlled – before and after September 2008. They account for 60% of the total credit supplied by retail banks. Results indicate that government control over two of the largest banks, supposedly an asset for crisis management, may have had higher welfare costs than assumed. We find no evidence of asymmetry in adjustments of retail rates charged by private and government-controlled banks.